Arenobufagin-loaded PEG-PLA nanoparticles for reducing toxicity and enhancing cancer therapy. (31st December 2023) - Jiaying, Yang; Bo, Sun; Xiaolu, Wei; Yanyan, Zhou; Hongjie, Wang; Nan, Si; Bo, Gao; Linna, Wang; Yan, Zhang; Wenya, Gao; Keke, Luo; Shan, Jiang; et al.
Abstract: Arenobufagin (ArBu) is a natural anticancer drug with good anti-tumor effects, but its clinical applications and drug development potential are limited due to its toxicity. The purpose of this study is to reduce the toxic side effects of ArBu and improve the efficacy of tumor treatment by incorporating it into poly(ethylene glycol)-b-poly (lactide) co-polymer (PEG-PLA). ArBu@PEG-PLA micelles were prepared by a thin film hydration method. The optimized micelles were characterized by size, stability, drug loading, encapsulation rate, and drug release. The tumor-inhibition efficacy of the micelles was evaluated on A549 cells and tumor-bearing mice. The ArBu@PEG-PLA micelles have good drug-loading capacity, release performance, and stability. They can accumulate at the tumor site through the EPR effect. The micelles induce apoptosis through a mitochondrial apoptosis pathway. Compared with the free ArBu, the ArBu@PEG-PLA micelles had lower toxicity and higher safety in the acute toxicity evaluation experiment. The in vivo anti-tumor experiment with tumor-bearing mice showed that the tumor-inhibition rate of ArBu@PEG-PLA micelles was 72.9%, which was 1.28-fold higher than that of free ArBu (57.1%), thus showing a good tumor treatment effect. This study indicates that ArBu@PEG-PLA polymeric micelles can significantly improve the toxicity and therapeutic efficacy of ArBu. These can lead to a new therapeutic strategy to reduce the toxicity of ArBu and enhance tumor treatment.